CHI '06 Extended Abstracts on Human Factors in Computing Systems 2006
DOI: 10.1145/1125451.1125533
|View full text |Cite
|
Sign up to set email alerts
|

AuraOrb

Abstract: One of the problems with notification appliances is that they can be distracting when providing information not of immediate interest to the user. In this paper, we present AuraOrb, an ambient notification appliance that deploys progressive turn taking techniques to minimize notification disruptions. AuraOrb uses eye contact sensing to detect user interest in an initially ambient light notification. Once detected, it displays a text message with a notification heading visible from 360 degrees. Touching the orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…8, a different picture emerges in the pruned dataset, as the response times between all ALS settings appear similar, except AL3 (which had the fewest extreme response time events). Repeating the same analysis for the pruned dataset, we find that a Friedman two-way analysis of variance, showed that the observed differences are statistically significant (χ 2 (3) = 15.360, p < 0.01). Further pairwise examination with posthoc Bonferroni-corrected Wilcoxon Signed Rank tests, resulting in a p-value threshold of p = 0.008, confirmed that the differences were statistically significant between AL1-AL3 (Z = 3.383, p = 0.001), AL2-AL3 (Z = 3.733, p = 0.000) and AL3-AL4 (Z = 2.993, p = 0.003), thereby concluding that the slow pulsing light is actually the least noticeable of the four combinations (all others having no statistically significant differences).…”
Section: Experiments Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…8, a different picture emerges in the pruned dataset, as the response times between all ALS settings appear similar, except AL3 (which had the fewest extreme response time events). Repeating the same analysis for the pruned dataset, we find that a Friedman two-way analysis of variance, showed that the observed differences are statistically significant (χ 2 (3) = 15.360, p < 0.01). Further pairwise examination with posthoc Bonferroni-corrected Wilcoxon Signed Rank tests, resulting in a p-value threshold of p = 0.008, confirmed that the differences were statistically significant between AL1-AL3 (Z = 3.383, p = 0.001), AL2-AL3 (Z = 3.733, p = 0.000) and AL3-AL4 (Z = 2.993, p = 0.003), thereby concluding that the slow pulsing light is actually the least noticeable of the four combinations (all others having no statistically significant differences).…”
Section: Experiments Resultsmentioning
confidence: 76%
“…In our case, the dependent variable was "Modality", since we try to predict the desired modality depending on the other context attributes. For experiment 1 participants, the final model rejects the null model hypothesis (χ 2 (52) = 808.042, p < 0.01) and demonstrates a good model fit (Pearson χ 2 (144) = 77.655, p = 1.00). However, the pseudo R 2 value is 0.399 (Nagelkerke), showing that only part of the variance in declared preferred modality is explainable by the contextual factors Task, Location, Social and Application Type.…”
Section: Multinominal Logistic Regressionmentioning
confidence: 77%
See 3 more Smart Citations